Evaluation of Regional Regulations on Maghrib Qur'an Recitation: A Comparative Study of Local Governments in Indonesia - Indira Sri Rejeki; Jumanah, Jumanah; Lisna Amalia; Zahrotun Nafiah; Rilanda Dwi Agustin (Sean Institute, 2025)
The Regional Regulation (Perda) on Maghrib Qur’an Recitation is a form of local policy aimed at fostering religious character and enhancing Qur’anic literacy among the community, particularly the younger generation. The time between Maghrib and Isha prayers is considered strategic and conducive for spiritual activities and moral development. This study aims to examine the urgency of implementing the Perda Maghrib Mengaji and its impact on character building among children and adolescents. Using a literature review and policy analysis approach, the findings reveal that this regulation has a positive impact in forming good habits, strengthening children's connection with the Qur’an, and preventing involvement in negative activities after Maghrib. However, the success of its implementation greatly depends on the support of parents, educational institutions, community leaders, and the availability of supporting facilities from local governments. Cross-sectoral synergy is required to ensure that the Perda Maghrib Mengaji becomes not just symbolic, but deeply rooted as a cultural practice in society.